Adhesion evaluation of thin films to dielectrics in multilayer stacks: A comparison of four-point bending and stressed overlayer technique. (15th February 2021) - Lassnig, A.; Putz, B.; Hirn, S.; Többens, D.M.; Mitterer, C.; Cordill, M.J.
Abstract: Assessing the interfacial strength of multilayered structures is crucial to ensure the reliability of such components. Two widely used tests, four-point bending (4PB) and the stressed overlayer (SOL) technique, are juxtaposed and employed in this study to determine adhesion of WTi on borophosphosilicate glass (BPSG) implemented in a model multilayer material stack with representative materials encountered in microelectronic applications including silicon, ductile metallic films and soft polyimide layers. The applicability and reproducibility of both methods is discussed in this paper including a detailed analysis of the stress evolution of the delaminating WTi using X-ray diffraction. While both adhesion measurement techniques reveal comparable adhesion energies for the WTi-BPSG interface, namely (9.4 ± 0.6) J/m 2 and (10.1 ± 1.0) J/m 2 for 4PB and SOL, respectively, we come to the conclusion that 4PB allows to integrally test the entire stack on a larger scale and SOL allows to determine the weakest site of the interface on a local scale. Both suggested methods are promising for future sub-micrometer thin film designs in complex multilayered structures since they are easy to perform and allow for a good statistical output of the results. Graphical abstract: Unlabelled Image Highlights: A model multimaterial stack was designed to integrally test critical interfaces in microelectronic devices. Using 4 point bending the weakest interface, WTi-BPSG, was identified revealing an energy release rate of (9.4±0.6) J/m 2 . The WTi-BPSG adhesion was also determined using a stressed overlayer on top of WTi leading to the mixed mode adhesion energy (10.1±1.0) J/m 2 . XRD measurements of the WTi revealed similar stresses regardless of layer setup, allowing a comparison of these test techniques.